helps you write and speak natural English (London, 2002)
Longman Language Activator (second edition): The only book that can lead students to exactly the right word or phrase- even if they have never heard it before, includes: *Clear simple headings *Helps students choose the right word by helping them understand the differences in meaning between words with similar meanings *Detailed definitions and natural examples show students the correct word to use *Students learn how to use their new word or phrase correctly using the collocations and phrases given for each meaning
Keywords: Dictionary; English